Unlocking the potential of engineered microbes in immunotoxin-based cancer therapy - Wang, Quan; Cao, Rui; Xie, Yuxing; Zhang, Zhuoyi; Li, Xianguo; Zhang, Yan; Luo, Haolin; Yao, Hui; Xue, Ping; Ni, Shuai (Frontiers in Microbiology, 2025)
Immunotoxins (ITs), as targeted cancer therapies, confront limitations including off-target effects, immunogenicity, and inadequate tumor penetration, hindering clinical translation. Advances in tumor microenvironment (TME) understanding and genetic engineering have enabled engineered microorganisms such as attenuated Salmonella, E. coli Nissle 1917, and modified eukaryotic platforms (e.g., yeast, microalgae) to colonize tumors and act as efficient hosts for IT production. By integrating ITs into these microbes and employing precise circuits (e.g., phage lysis systems, signal peptide fusions), controlled secretion of recombinant immunotoxins (RITs) can be achieved. Balanced-lethal systems further enhance plasmid stability for sustained therapeutic delivery. This review highlights strategies leveraging engineered microbes to amplify IT efficacy, exemplified by preclinical successes like Salmonella-delivered TGFα-PE38 and E. coli-expressed anti-PD-L1-PE38. However, challenges persist, including dynamic TME interactions, systemic infection risks, manufacturing complexities and regulatory uncertainties demand resolution. By synergizing microbial targeting with RIT, this approach offers transformative potential for cancer therapy, yet requires multidisciplinary innovation to address technical, safety, and regulatory barriers for clinical adoption.